Unconventional Nuclides for Radiopharmaceuticals - Jason P. Holland; Matthew J. Williamson; Jason S. Lewis (Molecular Imaging)
Rapid and widespread growth in the use of nuclear medicine for both diagnosis and therapy of disease has been the driving force behind burgeoning research interests in the design of novel radiopharmaceuticals. Until recently, the majority of clinical and basic science research has focused on the development of 11 C-, 13 N-, 15 O-, and 18 F-radiopharmaceuticals for use with positron emission tomography (PET) and 99m Tc-labeled agents for use with single-photon emission computed tomography (SPECT). With the increased availability of small, low-energy cyclotrons and improvements in both cyclotron targetry and purification chemistries, the use of “nonstandard” radionuclides is becoming more prevalent. This brief review describes the physical characteristics of 60 radionuclides, including β + , β −− , γ-ray, and α-particle emitters, which have the potential for use in the design and synthesis of the next generation of diagnostic and/or radiotherapeutic drugs. As the decay processes of many of the radionuclides described herein involve emission of high-energy γ-rays, relevant shielding and radiation safety issues are also considered. In particular, the properties and safety considerations associated with the increasingly prevalent PET nuclides 64 Cu, 68 Ga, 86 Y, 89 Zr, and 124 I are discussed.